Use of regression analysis to forecast cash flows - W. G. Klerck; L. E. Birkholtz (South African Journal of Business Management, 1984)
In this article the need to forecast the cash flows of a corporation is discussed. Although many corporations operate on a decentralized basis to a greater or lesser degree the cash resources of the corporation are often controlled from head office. The system is cash receipts are remitted to the head office treasurer on a daily, weekly, or monthly basis and he undertakes to make funds available. Owing to the size of many corporations the treasurer is far removed from activities at the branch level and it is not unknown for him to experience an unexpected inflow or outflow of funds. It is also often taken for granted by the operations' accountants that the corporate treasurer will always have sufficient funds to place at their disposal. This lack of communication can result in difficulties in providing the operations with the required funds. It is therefore necessary that the treasurer forecast his future cash position in order to have adequate cash resources at his disposal to meet the requirements of the operations over the short term. In order to assist the treasurer in making short term forecasts a model using regression analysis was developed.
Keywords: 650